Misi Allah Dalam Perintahnya Pada Keluaran 19:21-25 Dan Implementasinya Pada Konteks Saat Ini - Yusuf L. M. (Views : Jurnal Teologi dan Biblika, 2023)
Abstract: The basis of God's mission for the Gospel message often refers to the Great Commission of Jesus in the New Testament. The Old Testament context is very rarely used as a reference in laying the foundation of God's mission. Exodus 19:21-25, in Moses' dialogue with God on Mount Sinai in preparation for accepting the Sinai covenant becomes the basic context of God's Mission. The verb 'go', 'come down' in imperative form is used by God in the text to be the main emphasis and binding to become the basis of God's mission to the Israelites. This research uses qualitative methods with a library analysis approach such as interaction with primary sources such as Bible grammar books, commentary books, theological study books and articles published offline and online. The results of the analysis found that through the Sinai covenant, God showed how holy and glorious God is in His nature. The Israelites as God's mediators in redemptive history are required to respect and maintain the Sinai covenant. This is the basis for the people of Israel as God's chosen nation to live in a way that pleases the holy God. In the history of redemption, the Israelites were worthy and approved by God through the Sinai covenant to carry out His mission on this earth. This is the standard for today's church to carry out the task of preaching the Gospel, upholding the values ​​of sincerity, purity of heart, prioritizing maintaining God's holiness. Abstrak: Dasar misi Allah untuk pekabaran Injil sering mengacu kepada mandat Agung Yesus dalam perjanjian baru. Konteks Perjanjian Lama sangat jarang dijadikan rujukan dalam meletakkan dasar misi Allah. Keluaran 19:21-25, dalam dialog Musa dengan Allah di atas gunung Sinai dalam rangka persiapan menerima perjanjian Sinai menjadi konteks dasar Misi Allah. Kata kerja ‘pergilah’, ‘turunlah’ dalam bentuk imperative digunakan Allah dalam teks menjadi penekanan utama sekaligus mengikat untuk menjadi dasar misi Allah terhadap bangsa Israel. Riset ini menggunakan metode kualitatif dengan pendekatan analisis kepustakaan seperti interaksi terhadap sumber primer seperti buku tata Bahasa Alkitab, buku tafsir, buku kajian teologi serta artikel yang terpublikasi secara offline maupun online. Hasil analisis ditemukan bahwa melalui perjanjian Sinai, Allah memperlihatkan betapa kudusnya dan mulianya Allah dalam natur-Nya. Umat Israel sebagai mediator Allah dalam sejarah penebusan dituntut untuk menghormati dan menjaga perjanjian Sinai. Hal ini menjadi dasar bagi umat Israel sebagai bangsa pilihan Allah untuk hidup berkenan kepada Allah yang kudus. Dalam sejarah penebusan, bangsa Israel dilayakan dan diperkenan Allah melalui perjanjian Sinai untuk melaksanakan misi-Nya di bumi ini. Ini menjadi standar bagi gereja masa kini untuk menjalankan tugas pekabaran Injil, menjunjung tinggi nilai ketulusan, kemurnian hati, mengutamakan menjaga kekudusan Allah.